2005
DOI: 10.1097/01.brs.0000157476.16579.a2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Exostoses

Abstract: Spinal exostoses are more common than reported previously. Patients with MHE that present with back pain or neurological symptoms should produce a high index of suspicion. Evaluation should include both computed tomography and magnetic resonance imaging to define the origin of the exostosis and the presence of neural structure compression. Surgical excision should be preformed en bloc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 55 publications
0
32
0
1
Order By: Relevance
“…All levels of vertebral column can be involved, but the site most affected by isolated osteochondromas is C1 and for the multiple forms C2 [12, 13]. Spinal osteochondromas usually arise from the posterior elements that are the secondary ossification centers, and most commonly near the tips of the spinous processes [10].…”
Section: Discussionmentioning
confidence: 99%
“…All levels of vertebral column can be involved, but the site most affected by isolated osteochondromas is C1 and for the multiple forms C2 [12, 13]. Spinal osteochondromas usually arise from the posterior elements that are the secondary ossification centers, and most commonly near the tips of the spinous processes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal osteochondroma is a rare phenomenon and can originate as a solitary lesion or as a part of HME. Although the incidence of spinal osteochondroma in HME had been estimated at approximately 3% to 9% of patients with HME [ 1 , 10 ], Roach et al [ 7 ] reported that thirty (68%) of the forty-four patients with HME had exostoses arising from the spinal column and twelve (27%) had lesions encroaching into the spinal canal in 2009. They concluded that the risk a patient with HME had a lesion within the spinal canal is much higher than previously suspected.…”
Section: Discussionmentioning
confidence: 99%
“…A sudden increase in lesion size or the development of new-onset pain suggests malignant transformation [12,13]. Bess et al [15] emphasised that preoperative radiographic evaluation should consist of MR and CT imaging in order to provide optimal information about the lesion, which aids in surgical planning [3]. Radiologic findings may show consistent growth of exostoses after closure of the growth plate, alterations in surface delineation in comparison with previous radiographic studies, internal lytic areas, erosion or destruction of adjacent bones, and the presence of soft tissue masses containing scattered or irregular calcifications [15,16].…”
Section: Discussionmentioning
confidence: 99%